More ingredients for an Altarelli cocktail at MiniBooNE - Kevin J. Kelly; Joachim Kopp (Journal of High Energy Physics, 2023)
Abstract The MiniBooNE excess persists as a significant puzzle in particle physics. Given that the MiniBooNE detector cannot discriminate between electron-like signals and backgrounds due to photons, the goal of this work is to study photon backgrounds in MiniBooNE in depth. We first consider a novel single-photon background arising from multi-nucleon scattering with coherently enhanced initial or final state radiation. This class of processes, which we dub “2p2hγ” (two-particle–two-hole + photon) can explain ~40 of the ~560 excess events observed by MiniBooNE in neutrino mode. Second, we consider the background from neutral-current single-π 0 production, where two photons from π 0 → γγ decay are mis-identified as an electron-like shower. We construct a phenomenological likelihood that reproduces MiniBooNE’s π 0 → γγ background faithfully. Even with data-driven background estimation techniques, we find there is a residual dependence on the Monte Carlo generator used. Our results motivate a reduction in the significance of the MiniBooNE excess by 0.4σ.